PENENTUAN RUTE TRANSPORTASI DENGAN METODE SAVING MATRIX PADA PG MADUKISMO, YOGYAKARTA - Ika Putri Rahmasari; Pandi Pardian (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Increasing sugar mill productivity one of them is done by making improving the process of cutting and transportation sugarcane from the land until the sugar mill. PG Madukismo has implemented that sugarcane cutting and hauling pattern to fulfill raw material in the mill however that's not running well because it is still based on the sugarcane cutting schedule of each region, therefore, this study is conducted on based on sugarcane transportation activities. The goal of this study was to determine the optimum transportation route in the process of transporting sugarcane raw materials to PG Madukismo. This study uses saving matrix analysis. Results of this study showing that the vehicles used are 222 and 4 groups of transportation areas to provide a saving distance of 373.9 Km